2015
DOI: 10.1098/rsif.2015.0446
|View full text |Cite
|
Sign up to set email alerts
|

‘Super' or just ‘above average'? Supershedders and the transmission of Escherichia coli O157:H7 among feedlot cattle

Abstract: Supershedders have been suggested to be major drivers of transmission of Escherichia coli O157:H7 (E. coli O157:H7) among cattle in feedlot environments, despite our relatively limited knowledge of the processes that govern periods of high shedding within an individual animal. In this study, we attempt a data-driven approach, estimating the key characteristics of high shedding behaviour, including effects on transmission to other animals, directly from a study of natural E. coli O157:H7 infection of cattle in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 49 publications
7
37
0
1
Order By: Relevance
“…In addition to transportation and lairage, there are also animal-related factors affecting the prevalence of hide contamination in cattle. For example, the presence of 'supershedders' in the pens of feedlot cattle can significantly increase transmission [42] and the prevalence of hide contamination [43]. Similarly, Jacob et al [44] found a significant correlation between hide prevalence within truckloads (a cohort of adult cattle transported and lairaged together) and the presence of high shedders (>5 × 10 4 CFU/g faeces) in truckloads, indicating that the levels of faecal E. coli shed during transportation and lairage also have an impact on the prevalence of hide contamination among slaughter cattle.…”
Section: Epidemiology and Infection 1097mentioning
confidence: 99%
“…In addition to transportation and lairage, there are also animal-related factors affecting the prevalence of hide contamination in cattle. For example, the presence of 'supershedders' in the pens of feedlot cattle can significantly increase transmission [42] and the prevalence of hide contamination [43]. Similarly, Jacob et al [44] found a significant correlation between hide prevalence within truckloads (a cohort of adult cattle transported and lairaged together) and the presence of high shedders (>5 × 10 4 CFU/g faeces) in truckloads, indicating that the levels of faecal E. coli shed during transportation and lairage also have an impact on the prevalence of hide contamination among slaughter cattle.…”
Section: Epidemiology and Infection 1097mentioning
confidence: 99%
“…Moreover, inferences derived from cross-sectional studies can mislead control efforts. For example, longitudinal studies of Escherichia coli O157 in cattle, thought to be maintained by persistently infected supershedders, revealed that the pathogen may be serially shed by many individualsin other words, different individuals take turns at supershedding (Spencer et al 2015). If supershedding is not a stable individual-host characteristic, then targeted interventions based on specific individuals will fail.…”
Section: Introductionmentioning
confidence: 99%
“…Such evidence supports suggestions that the diversity and composition of the cattle gut microbiome are important factors in controlling pathogen carriage (Munns et al., ). However, variation in feeds and administration of probiotics had little, if any, positive effect on “Super shedders” in other studies (Spencer, Besser, Cobbold, & French, ). Thus, the relationship between gut microbiome, diet and STEC carriage requires considerable further investigation.…”
Section: Prevention and Controlmentioning
confidence: 68%
“…(Munns et al, 2015). However, variation in feeds and administration of probiotics had little, if any, positive effect on "Super shedders" in other studies (Spencer, Besser, Cobbold, & French, 2015 Cattle hides are a particular source of carcass contamination, and the levels of STEC on hides at slaughter are a good predictor of meat contamination after processing (Wheeler, Kalchayanand, & Bosilevac, 2014). Interestingly, the diversity of the commensal microbial population of cattle hides appears to be important in determining the risk of contamination with STEC strains (Chopyk et al, 2016).…”
Section: Preven Tion and Controlmentioning
confidence: 92%